Two-dimensional NMR characterization of gas–water distribution in tight sandstone reservoirs: a case study from the Ordos Basin, China - Zhang, Ran; Chen, Xinyi; Sun, Xin; Ge, Xiang; Du, Huanfu; Yao, Mengmeng (Frontiers in Earth Science, 2025)
Tight sandstone reservoirs exhibit low porosity, low permeability, significant heterogeneity, and complex gas-water distribution patterns, posing significant challenges for conventional logging methods in accurate gas reservoir identification. Incomplete comprehension of nuclear magnetic signal responses under varying temperature, pressure, and pore structure conditions further limits the precision of fluid identification through nuclear magnetic logging. To resolve these limitations, this study systematically investigates the distribution and dynamic behavior of methane gas and water in tight sandstone through nuclear magnetic resonance (NMR) analysis of samples under saturated water, saturated methane, centrifugation, and drying conditions, conducted at original geothermal pressures. Combined with water-flooding gas experiments, the study elucidates the variation in nuclear magnetic responses of tight sandstone under different pressure and temperature conditions. The research implements quantitative analysis of displacement pressure effects on fluid component redistribution during water invasion processes, ultimately establishing a two-dimensional NMR gas-water identification model for tight sandstone that enables both visual interface demarcation and differential substance characterization, while offering technical support for reservoir exploration and development.